Agro-environmental and socioeconomic consequens of el niño very strong: adaptation and mitigation alternatives for rainfood maize (Zea mays L.) farming families in Ciudad Darío (Nexo Revista Científica, 2022)
A very strong El Niño drastically affects the peasant families that grow corn. This research focuses on an estimation of the agro-environmental and socioeconomic consequences of maize production during a very strong El Niño that contributes to proposing agroecological technologies and practices for the redesign of agroecosystems in the municipality of Ciudad Darío. The effect of water needs on the phenological phases of the NB-S maize variety was determined, in the primera (1982, 1983 and 1997) and postrera (1982 and 1997) seasons. A documentary analysis was carried out to assess the agro-environmental and socioeconomic consequences, and to propose agroecological technologies and practices. The water deficit caused by the very strong El Niño drought in 1982-1983 and 1997-1998 affected the yield and production of maize, which implies more impoverishment, food insecurity, deterioration of health, reduced availability of water from well during the dry period, soil degradation, effects on the quality of the landscape and the biodiversity of agroecosystems 37 agroecological technologies and practices are proposed to gradually transform the agroecosystems of Ciudad Darío, in which rain-fed maize is grown.